Temple of presence: the Christological fulfillment of Ezekiel 40-48 in Revelation 21:1-22:5 - Robinson, Andrea L. (Wipf & Stock, 2019)
Introduction -- State of research. Intertextual foundations ; John's use of the OT and Ezekiel ; Contribution to scholarship -- The temple vision of Ezekiel. The unity of Ezekiel ; Interpretations of the temple vision -- Temple and Messiah in literature predating Revelation. Tobit ; Baruch ; The Testaments of the Twelve Patriarchs ; 1 Enoch ; 2 Enoch ; Jubilees ; Sibylline Oracle.